GSM based gas leak monitoring system - Nozad Mahmood, Sarmad; Ishak, Asnor Juraiza; Hussain, Salam T. (International University of Sarajevo, 2019)
This paper used a safe wireless module to detect a gas leakage. The module is household use application where home fires or Liquefied Petroleum Gas (LPG) are classified as the reason of the disasters. The LPG is considered as the most inflammable gases that can ignite fires even in the far distances where gas leak exists. The module can be applied in several places particularly in the fabrications that depend mainly on LPG gas to manage their works. According to the facilities offered by this work, the whole module is functionally separated to perform two tasks identified by gas leak monitoring and the precautions taken accordingly. The module reads the gas sensor in a proposed environment to discover whether gas concentration exceeds a specified range. The system will be activated once the module detects that the gas concentration is altered, and accordingly the control action turns the alarm system alongside with air puller device ON, and sends a warning SMS to a certain recipient using GSM module.